2015
DOI: 10.1007/s10561-015-9530-9
|View full text |Cite
|
Sign up to set email alerts
|

Cryopreserved amniotic membrane as transplant allograft: viability and post-transplant outcome

Abstract: Amniotic membrane (AM) transplantation is increasingly used in ophthalmological and dermatological surgeries to promote re-epithelialization and wound healing. Biologically active cells in the epithelial and stromal layers deliver growth factors and cytokines with anti-inflammatory, anti-bacterial, anti-immunogenic and anti-fibrotic properties. In this work, confocal microscopy was used to show that our cryopreservation protocol for AM yielded viable cells in both the stromal and epithelial layers with favorab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 38 publications
(66 reference statements)
1
16
0
Order By: Relevance
“…VCAM retrospective and prospective clinical studies reported positive clinical outcomes in patients with acute and chronic wounds of various etiologies and in a variety of surgical procedures without adverse events attributed to VCAM application [ 22 25 ]. Data from these VCAM clinical studies are consistent with other reports describing the clinic use of DMSO-cryopreserved viable AM prepared using different cryopreservation protocols [ 48 , 49 ]. In a randomized controlled clinical trial, 75% of pressure ulcers were closed in the cryopreserved AM group versus 0% in the control group [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…VCAM retrospective and prospective clinical studies reported positive clinical outcomes in patients with acute and chronic wounds of various etiologies and in a variety of surgical procedures without adverse events attributed to VCAM application [ 22 25 ]. Data from these VCAM clinical studies are consistent with other reports describing the clinic use of DMSO-cryopreserved viable AM prepared using different cryopreservation protocols [ 48 , 49 ]. In a randomized controlled clinical trial, 75% of pressure ulcers were closed in the cryopreserved AM group versus 0% in the control group [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a randomized controlled clinical trial, 75% of pressure ulcers were closed in the cryopreserved AM group versus 0% in the control group [ 48 ]. A different retrospective study reported positive outcomes with DMSO-cryopreserved viable AM for a broad variety of ocular diseases and dermatological defects without adverse events [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Penetrant CPAs, such as DMSO, displace the internal water from the cell, minimizing the intracellular ice crystal formation while, non-penetrant CPAs, such as sucrose, act from the outside of the cells, promoting their dehydration 23 . DMSO shows several disadvantages in the preservation process such as toxicity or loss of multipotency 41 , but its replacement is difficult since no other CPA has shown the same results maintaining embedded cell viabilities after cryopreservation 42 . However, the combination of DMSO and sucrose enhance also the post-thawing viability of human MSCs 43 , 44 .…”
Section: Resultsmentioning
confidence: 99%
“…Our independent results were similar to other published findings that compared cryopreserved and lyopreserved amniotic tissue from this construct. 18 The primary outcome of the prospective cohort study was to evaluate the proportion of ulcers that achieved complete closure in 12 weeks in patients treated with LAM. The proportion of patients who achieved complete closure was 48%.…”
Section: Discussionmentioning
confidence: 99%